Identifikasi Pengenalan Lagu Daerah dalam Pembelajaran Sebagai Muatan Lokal di PAUD Kecamatan Sandubaya Kota Mataram - Arrum Fitrianingsih; Baik Nilawati Astini; Ika Rachmayani; Baiq Nada Buahana (Indonesian Journal of Elementary and Childhood Education, 2023)
Folk songs are one of the ancestral legacies that must be preserved, but over time folk songs have regressed. This study aims to identify the introduction of regional songs in learning in PAUD Sandubaya District, Mataram City so that they can find out what songs have been introduced in learning activities, what regional songs are dominantly used or sung and how to introduce regional songs by teachers to students in learning activities. The type of research used isurvey research with descriptive quantitative methods. The research subjects used were 9 PAUD teachers in Sandubaya District. The data collection methods used are observation methods, questionnaires and documentation. As for the type of analysis using percentages according to Arikunto. The results of this study found that PAUD teachers in Sandubaya District, Mataram City had introduced regional songs to students. The folk songs that have been introduced are: the song Inaq Tegining Amaq Teganang, Tunas Pamit, Kadal Nongaq, Kembang Mawar, Anak Kambing Saya, Ampar-ampar Pisang, Yamko Rambe Yamko, Awas Batur, Lampak-lampak, Bungong jeumpa, Kampuang Nan Jauh Dimato and the most dominant folk song introduced to students is the song Inaq Tegining Amaq Teganang with a frequency of answers of 89%. In the introduction of regional songs, there are several steps taken by teachers including: using media and methods, adjusting to the theme, introducing 1-3 songs for 1 semester, introducing songs to opening activities, istrahat and cultural saturdays, introducing songs repeatedly and explaining the meaning of regional songs.